South African Airways (SAA) : navigating turbulent skies - Beswick, Claire; Mosala, Thabo ([London] : SAGE, 2016)
In April 2010, Siza Mzimela was appointed as CEO of the government-owned South African Airways (SAA). As far back as 2007, the South African government had issued the airline with an ultimatum - 'get your affairs in order or you are on your own'. Yet the airline was still in a financially disastrous position. Mzimela knew that she had to come up with a workable strategy for SAA, and wondered what the organisation had to do to turn itself around.
Originally Published in: Beswick, C., & Mosala, T. (2013). South African Airways (SAA): Navigating Turbulent Skies. WBS-2013-22. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; South African Airways; Organizational change -- Case studies; Strategic planning -- Case studies; Leadership -- Case studies